Diurnal water use patterns for low-cost houses with indigent water allocation: a South African case study - Pretorius, Dian; Crouch, Melissa Lauren; Jacobs, Heinz Erasmus (Journal of water, sanitation, and hygiene for development, 2019)
The diurnal water use patterns are of interest to hydraulic modellers, as these patterns are required for the design of water distribution systems. An extensive body of literature is available with regard to daily, weekly and seasonal diurnal water use patterns of typical suburban houses. However, the characteristics of South African low-cost houses, the socio-economic status of the consumers and the level of water service to such houses differs from typical western suburban houses reported on elsewhere. Notable differences include the limited access to heated water and negligible garden irrigation at the low-cost houses. Knowledge of water use in low-cost houses, which are prevalent in South Africa, is limited. To reduce this lack of knowledge, approximately 2.5 million flow records were collected over a period of 3 years from a sample of 14 low-cost houses as part of this empirical case study. Subsequently, a diurnal water use pattern was constructed for the selected low-cost houses at 15-minute and 1-hour resolution. The diurnal pattern is useful for hydraulic modellers when data that represent extended period time simulation of water networks in low-cost housing developments is required.